Visco-modified osculating magnetic and electric flux surfaces in the normal direction - Körpınar, Talat; Demirkol, Rıdvan Cem; Körpınar, Zeliha (Taylor and Francis Ltd., 2025)
In this manuscript, we investigate a new technique to describe the tangent, principal normal, and binormal osculating magnetic and electric flow density in the normal direction in the ordinary space. Based on the computed flow density, we determine the Frenet–Serret vectors of the osculating magnetic and electric flow phase in the normal phase. Then, we consider the modified visco Heisenberg ferromagnetic model to observe the variation when we compare Frenet–Serret vectors of the osculating magnetic and electric flow phase due to the modified visco Heisenberg ferromagnetic. Finally, we determine the existence conditions for describing the field vectors flux surfaces under the osculating evolution equations in the normal direction. © 2025 Elsevier B.V., All rights reserved.
Keywords: Ferromagnetism; Flow Density; Flow Phase; Osculating Motion; Visco Heisenberg Model; Ferromagnetic Materials; Insulation; Vectors; Electric Flow; Flow Density; Flow Phase; Flux Surfaces; Heisenberg; Heisenberg Models; Magnetic Flow; Normal Direction; Osculating Motion; Visco Heisenberg Model; Ferromagnetism